PENERAPAN METODE PEMECAHAN MASALAH (PROBLEM SOLVING) UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG KOMPONEN PETA - Pristiwanto, - (Universitas Islam Darul Ulum, 2016)
The purpose of the research was to increase the students understanding on the components of the map. The data required in this study were obtained through observation of treatment of active learning, and formative tests. This research used qualitative descriptive analysis technique that illustrates the fact or facts in accordance with the data obtained in order to determine the studentsâ learning outcomes achieved by students as well as to elicit the studentsâ responses in learning activities as well as activities of students during the learning process. The results of this research showed that the students understanding and mastery of the material that has been submitted by the teacher (the learning mastery increased from cycle I, II, and III) are respectively 67.64%, 77.35% and 91.17%. Thus, the learning method of problem solving could improve the studentsâ achievement.